2013
DOI: 10.1038/labinvest.2012.174
|View full text |Cite|
|
Sign up to set email alerts
|

The inhibitory action of PDCD4 in lipopolysaccharide/D-galactosamine-induced acute liver injury

Abstract: Programmed cell death 4 (PDCD4) acts as a tumor suppressor gene, which suppresses tumor growth, infiltration and metastasis. Our previous studies demonstrated that PDCD4 had an important role in the development of ovarian cancer and glioma. Recent studies show that PDCD4 is also involved in various inflammatory diseases. However, its exact effect on inflammation remains unclear. In our current study, we explored the role of PDCD4 in acute liver injury induced by lipopolysaccharide (LPS) and D-galactosamine (D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 49 publications
(60 reference statements)
0
19
0
1
Order By: Relevance
“…Wang et al (26) discovered that PDCD4 deficiency aggravated colitis via promoting the IL-6/STAT3 pathway in mice. However, Schmid et al (27) maintained that inflammation could induce the loss of PDCD4, and Wang et al (8) indicated that PDCD4 upregulation inhibited inflammatory responses by inhibiting NF-κB and MAPK signaling pathway activation in an LPS/ d -GalN-induced mouse model. Therefore, PDCD4 may be closely associated with inflammatory responses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al (26) discovered that PDCD4 deficiency aggravated colitis via promoting the IL-6/STAT3 pathway in mice. However, Schmid et al (27) maintained that inflammation could induce the loss of PDCD4, and Wang et al (8) indicated that PDCD4 upregulation inhibited inflammatory responses by inhibiting NF-κB and MAPK signaling pathway activation in an LPS/ d -GalN-induced mouse model. Therefore, PDCD4 may be closely associated with inflammatory responses.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that AA treatment effectively inhibited L/D-induced JNK, ERK, P38, P65, and IκBα phosphorylation and blocked IκBα degradation. Moreover, PDCD4 downregulation was reported to promote LPS-stimulated secretion of proinflammatory mediators, and PDCD4 deficiency exacerbated the sensitivity of liver injury in L/D-induced mice by inducing MAPK and NF-κB pathway activation (8, 43). Our studies revealed that L/D exposure dramatically decreased PDCD4 protein expression, whereas this effect was significantly suppressed by AA pretreatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated inflammatory cytokine productions were observed in mice of LPS/GalN-induced liver injury [17]. These inflammatory cytokines, especially TNF-α and IL-1β, have been known to play critical roles in the pathogenesis of liver injury [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…了肝细胞的凋亡和坏死, 在血清和肝组织中提高了IL-6, MCP-1, TNF-α, IL-1β等多种促炎性细胞因子的表达 水平 [76] . [74,75] ; 在高脂诱导的肥胖模型中, PDCD4主要是通过调控巨噬细胞极化和脂质代谢发 挥作用 [48] ; 在LPS诱导急性肝损伤模型和DSS诱导的 急性结肠炎模型中, PDCD4主要通过调节巨噬细胞的 功能发挥作用 [68,76] . 另有报道 [77] , IFN-α可通过p70 S6…”
Section: Pdcd4基因缺失的小鼠肝损伤更为严重 明显地促进unclassified